A separation [videorecording (DVD)] - Farhādī, Aṣghar, 1972-; Muʻādī, Paymān, 1972-; Ḥātamī, Laylā, 1970-; Bayat, Sareh, 1979- (Sony Pictures Classics, 2012)
A married couple are faced with a difficult decision - to improve the life of their child by moving to another country or to stay in Iran and look after a deteriorating parent who has Alzheimer's disease.